Flutes in the forefield of Nordenskiöldbreen, Svalbard - Vigdís Bjarnadóttir 1990- (2015)
Flutes are prominent glacial landforms and may be formed by either warm-based or polythermal glaciers. The area on which they form has the appearance of a field, ploughed parallel to glacier flow. Flutes have a low preservation potential because they are easily eroded by water and wind. Flutes have been studied in both alpine and arctic environments, all over the world. In this study flutes in the forefield of Nordenskiöldbreen, Svalbard were documented by describing their setting, morphology and sediment composition. Fabric measurements were performed and elongation ratios calculated. The results were then compared to measurements of flutes in glacial forefields in both Svalbard and Iceland. All this was done to get a general overview of the formation of flutes, to prove that the flutes must have been formed during the last advance, and to demonstrate that Nordenskiöld is indeed a polythermal glacier as has been mentioned in previous studies. Flútur eru áberandi landform sem myndast þegar annaðhvort þíðjökull eða fjölvarma jökull skríður fram. Svæði með flútum lítur oft út eins og akur sem plægður hefur verið samhliða flæði jökuls. Flútur varðveitast illa þar sem þær eru auðveldlega rofnar af vatni og vindi. Þær hafa verið rannsakaðar í bæði háfjalla- og heimskautaloftslagi um allan heim en í þessari rannsókn voru flútur á jökulsvæði Nordenskiöldbreen, Svalbarða, skoðaðar nánar. Upplýsingar sem fengust í felti um flúturnar voru skráðar, ásamt form- og setgerð þeirra. Gerðar voru veftu mælingar og hlutfall lengda flútanna reiknað. Niðurstöðurnar voru síðan bornar saman við mælingar gerðar á flútum frá bæði Svalbarða og Íslandi. Þetta var gert til þess að fá almennt yfirlit yfir myndun flúta, sanna að flúturnar hljóta að hafa myndast í síðustu framrás jökulsins og að Nordenskiöldbreen sé í raun fjölvarma jökull líkt og komið hefur fram í fyrri rannsóknum.